Design of the Boys Hostel at Kabale University. - Nuwagaba, Happiness (Kabale University, 2023)
This documentation is about the design of a two storied hostel at Kabale University. The ideas of this design were obtained from review of architectural textbooks, journals and building review reports. It also contains how our group intends and will carry out the design process of the hostel. The writing contains three chapters whereby; Chapter one is the introduction of the proposal that states the contents of the background of the university, how the problem was identified and why the project of hostel design was chosen ahead of others. Chapter two contains the literature review, works and related information by other scholars about design of structures. Chapter three outlines the methodology of how the project will be done; these are sequential methods for the process. Chapter four discusses the results and project discussions that involves details of the budget, work plan, appendices and reference